Protective effect of apoptosis signal-regulating kinase 1 inhibitor against mice liver injury - He, Ping; Zeng, Bo; Zhang, Xiao-Li; Fang, Dian-Liang; Zhou, Xia-Qia; Wan, Ke-Qiang; Tian, Wen-Guang (Asian Pacific journal of tropical medicine, 2016)
To explore the protective effect and its molecular mechanism of apoptosis signal-regulating kinase 1 (ASK1) inhibitor (GS-459679) on acetaminophen-induced liver injury in mice. The model of liver injury was established by administration of acetaminophen (APAP) (300 mg/kg, i.p.) on C57BL/6 mice. Forty-eight male C57BL/6 mice were randomly divided into four groups, consisting of control group, GS group (GS-459679, 30 mg/kg, i.p.), APAP-induced group, and GS combined with APAP-induced group. For GS combined with APAP-induced group, mice were treated with GS 30 min prior to administration of APAP. After mice were euthanized at 6 h or 12 h, respectively, serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were analyzed, and mRNA levels of TNF-α, IL-6 and IL-1β were tested. The activity of glutathione (GSH), oxidized GSH (GSSG) and malondialdehyde were quantified. In addition, ASK1, P-ASK1, JNK and P-JNK protein levels were tested in all groups. The ASK1 and P-ASK1 levels were up-regulated in APAP-induced group. Compared to the control group, serum levels of ALT and AST, and mRNA levels of TNF-α, IL-6 and IL-1β were increased in APAP-induced group. Meanwhile, the levels of MAD and GSSG, and the ratio of GSSG/GSH were higher and the JNK was activatedin APAP-induced group compared with that in control group. However, compared to APAP-induced group, GS combined with APAP-induced group displayed a decrease of protein expression levels of ASK1, P-ASK1 and P-JNK, a reduction of serum levels of ALT and AST, a decrease in TNF-α, IL-6 and IL-1β mRNA levels, and a low ration of GSSG/GSH. GS-459679 treatment effectively down-regulates ASK1 and P-ASK1 expression. Addition of GS-459679 decreases the generation of liver metabolites and inflammatory factors, reduces oxidative stress reaction, inhibits JNK activation, and then protects the responsiveness to APAP-induced liver injury.